Are you have to do now that I have some multiplication is 36+72 that will give you your answer
is it 42 or 4 and 2 separate
-6/5,-236/5 would be the minimum
(x - 1)(x - 2)(x + 2)
note that the sum of the coefficients 1 - 1 - 4 + 4 = 0
thus x = 1 is a root and (x - 1 ) is a factor
dividing x³ - x² - 4x + 4 by (x - 1)
x³ - x² - 4x + 4 = (x - 1)(x² - 4 ) (note (x² - 4 ) is a difference of squares )
x³ - x² - 4x + 4 = (x - 1)(x - 2)(x + 2)
(x - 1)(x - 2)(x + 2 ) =0
x - 1 = 0 ⇒ x = 1
x - 2 = 0 ⇒ x = 2
x + 2 = 0 ⇒ x = - 2
solutions are x = 1 or x = ± 2
The correct answer is 'Equation F can be written as 2d + 1 = 3d + 7'. In order to find the answer to a system of equations, the two equations must be set equal to each other. For instance, if we had the equations x = y + 1 and x = 3y - 1, we would set the two equations equal to one another to find the answer.
x = y + 1
x = 3y - 1
y + 1 = 3y - 1
1 = 2y - 1
2 = 2y
1 = y
x = y + 1
x = 1 + 1
<span>x = 2
We can use this to solve the set of equations above.
</span><span>2d + 1 = 3d + 7
</span>1 = d + 7
-6 = d
c = 2d + 1
c = 2(-6) + 1
c = -12 + 1
c = -11
Hope this helps!